On the relationship between procedural and declarative organizational memory and their effects on SME performance - Aminu, Mohammed Ibrahim; Mahmood, Rosli (Medwell Journals, 2016)
Although, knowledge integration has been theoretically conceptualized as a source of superior performance, very little attention is paid to investigate this relationship empirically especially in small and medium firms of developing countries. This study is designed to investigate the role of procedural memory (i.e., tacit knowledge) on the integration and development of declarative memory (i.e., explicit knowledge) and therefore the effects of these types of knowledge on SME performance on the platform of knowledge-based view.The 302 usable data was collected from corporate SMEs in Nigeria and thus the result was analyzed using partial least squares path modeling.The statistical data established the empirical evidence on the relationship between procedural and declarative knowledge as well as the effects of both of these forms of organizational knowledge or memory on performance. Consequently, the study concludes that SMEs' managers should invest in organizational knowledge for superior performance.Finally, the study suggested that future research may include other forms of knowledge assets and also take into cognizance with other components of performance.